Studies With Soft Corals – Recommendations on Sample Processing and Normalization Metrics - Pupier, Chloé A.; Bednarz, Vanessa N.; Ferrier-Pagès, Christine (Frontiers in Marine Science, 2018)
Soft corals (Octocorallia) often constitute the second most abundant macrobenthic group on many tropical and temperate reefs. However, the gelatinous and leather-like nature of their tissue and their variable hydroskeleton entails a number of problems for tissue homogenization and data normalization. An easy and fast protocol for tissue homogenization, as well as a normalization metric that can be used to perform inter-studies or inter-species comparisons, are thus needed. In this study, we tested whether the tissue sample state before processing (frozen vs freeze-dried samples) and the media used for tissue homogenization (0.2 µm filtered seawater; FSW vs milliQ water; DI) affects the quantitative measurements of tissue descriptors (chlorophyll, protein and Symbiodinium concentrations) in the model species Heteroxenia fuscescens. Furthermore, the suitability of dry weight (DW) and ash-free dry weight (AFDW) as size-normalizing metric was investigated across different soft coral species. Our results reveal that freeze-drying the samples and homogenizing them in DI water exhibited several benefits, namely enhancing chlorophyll and protein concentrations up to 50%, saving processing time and providing a more accurate determination of DW and AFDW. Overall, this optimized tissue processing protocol offers a more reliable quantification of tissue descriptors and reduces the chance of underestimating these parameters in soft corals. Finally, since the contribution of sclerites to the total DW of the colony can highly differ between species, we demonstrate that AFDW is a reliable metric for normalizing soft coral data, particularly when inter-species comparisons are made.